Conscientious objection in healthcare: neither a negative nor a positive right - Giubilini, A (Journal of Clinical Ethics, 2020)
Conscientious objection in healthcare is often granted by many legislations regulating morally controversial medical procedures, such as abortion or medical assistance in dying. However, there is virtually no protection of positive claims of conscience, that is, of requests by healthcare professionals to provide certain services that they conscientiously believe ought to be provided, but that are ruled out by institutional policies. Positive claims of conscience have received comparatively little attention in academic debates. Some think that negative and positive claims of conscience deserve equal protection in terms of measures that institutions ought to take to accommodate them. However, in this issue of The Journal of Clinical Ethics (JCE), Abram Brummett argues against this symmetry thesis. He suggests that the relevant distinction is not between negative and positive claims of conscience, but between negative and positive rights of conscience. He argues that conscientious refusals and positive claims of conscience are both already protected as negative rights of conscience, but that this does not require institutions to accommodate positive claims of conscience. In this article I will argue that both Brummett and the authors he criticizes share a wrong view about the existence of conscience rights in healthcare. I will argue that there is no right to conscientious objection in healthcare, whether positive or negative. Thus, contra Brummett, I argue that the question whether such rights are positive or negative is as irrelevant as the question whether the claims of conscience are positive or negative.